PENGARUH SOCIAL STORIES TERHADAP KETERAMPILAN SOSIAL ANAK DENGAN ATTENTION-DEFICIT HYPERACTIVITY DISORDER (ADHD) Studi Eksperimental Desain Kasus Tunggal di Sekolah Alam Ar-Ridho Semarang - Novita, Novita; Siswati, Siswati (Faculty of Psychology, Diponegoro University, 2010)
Among Attention-Deficit Hiperactivity Disorder (ADHD) diagnostic criteria is the obstacles in academic and social function across multiple setting. About 50% children with ADHD have difficulties to establish peer relationship, and made some impact to social skill deficit. Social stories can teach social skill to individu who have social problems. The aim of social stories is to provide the individual with a greater understanding of certain social situations. This research was held to identify the social stories influence toward social skill of children with ADHD. The research used single case experiment with A-B design. Participant selection was based on age, reading ability, Hiperactive Behavior Indonesian Child Rating Scale score, and Walker McConnel Social Competence and School Adjusment score. There are two partisipants that passed through all the criteria. The result of data analysis are (1) statistical analysis show there is no difference on frequency of target behavior after social stories treatment had given (asymp. signf. 0.242> 0.05 < 0.171) (2) statistical analysis show there is no difference on duration of target behavior after social stories treatment had given (asymp. signf. 0.272>0.05< 0.464) (3) participant #1 and participant #2 showed improvement tendency based on visual inspection to the target behavior graph (4) social stories can increase participant’s knowledge regarded how to do a behavior, but could not help participant to carried out their knowledge in to behavior yet. The conclusion of this research is social stories do not have influence toward social skill of children with ADHD. Social stories only influenced on cognitive level, could not foster participant to carried out the knowledge in to behavior yet.Keywords: social stories, social skill, ADHDPermalink :